The Factors Affecting on Financial Distress: Empirical Study of Energy Sector of Indonesia - Fatma Laila Ali; Lidiyawati Lidiyawati (Tinta Emas Publisher, 2025)
Financial distress is a state a company experiences before bankruptcy whereares financial performance in crysis situation on generating profit or payment current obligation. In line with the signal theory, financial distress can be indicated through management actions. This study aims to determine and predict the effects of profitability, leverage, and sales growth on financial distress. The study uses secondary data from 69 energy companies listed on Indonesia Stock Market during 2021-2023. The purposive sampling used for this research. Logistic regression analysis, conducted using SPSS 27, result that profitability has a negative effect on financial distress significantly, but leverage and sales growth do not have a significant positive effect. Thus, Return on Assets (ROA) is relevant to financial distress, but leverage and sales growth can be considered as variables that need to be explored in further fundamental research.. This finding can direct future research to explore more result trought use others sector and involved additional variables or extent the research periode. Specifically assessing the energy sector in investment activities can also be considered considering the average leverage value is more than 4 times the total equity value and profit is only at 0.15.